PERDAGANGAN KOPI VIETNAM DAN INDONESIA DI EMPAT NEGARA TUJUAN EKSPOR KOPI UTAMA: PENERAPAN MODEL CONSTANT MARKET SHARE - Atmadji, Eko; Priyadi, Unggul; Achiria, Siti (EP FEB UNS, 2019)
Vietnam and Indonesia dominate the world coffee trade, beside Brazil and Columbia. Coffee exports of these two countries are dominated by robusta coffee. The demand for robusta coffee increases along with the increasing the role of modern coffee makers and baristas in processing robusta coffee. This study employs Constant Market Share as a tool of analysis. The results of Constant Market Share calculations show that Vietnamese coffee and Indonesian coffee are still unable to compete with Arabica coffee. This can be seen from the effect of negative competitiveness for the coffee of the two countries. However, the results of calculating the effects of commodity composition, Vietnamese and Indonesian coffee are favored by coffee importers in the United States, Germany, Italy and Japan. In number of export value, Vietnamese coffee left behindIndonesian coffee in the United States, Germany and Italy. However, in Japan, Vietnamese and Indonesian coffee could not dominate each other. For Indonesia, Japan is the only major importer of coffee in the world that is expected to break the dominance of Vietnamese coffee. Nevertheless, the hope will get a considerable challenges from Japan and domestic itself.